Dinaphtho[1, 8‐bc:1′, 8′‐fg][1, 5]dithiocine Bisimide. Issue 3 (9th February 2021) - Tanaka, Yuki; Tajima, Keita; Fukui, Norihito; Shinokubo, Hiroshi
Abstract: V‐shaped π‐systems are attractive research targets in organic chemistry and materials science. Our group has recently demonstrated that the conceptual insertion of a heteroatom into a perylene bisimide (PBI) core is an effective guideline for the design of non‐planar PBI derivatives. Here we report the synthesis and properties of dinaphtho[1, 8‐ bc :1′, 8′‐ fg ][1, 5]dithiocine bisimide (DNDTBI), which represents a doubly sulfur‐inserted PBI derivative. The X‐ray diffraction analysis revealed that DNDTBI adopted a V‐shaped structure with a dihedral angle of 67°. DNDTBI exhibited higher electron‐donating ability than singly sulfur‐inserted PBI derivative owing to the antibonding interaction between the two neighboring sulfur atoms. The inversion barrier of the flipping motion of DNDTBI was ca. 30 kcal mol −1, indicating the rigid nature of the V‐shaped structure. Abstract : The synthesis and properties of dinaphtho[1, 8‐ bc :1′, 8′‐ fg ][1, 5]dithiocine bisimide (DNDTBI) is described . DNDTBI represents a doubly sulfur‐inserted perylene bisimide (PBI) derivative. DNDTBI adopted a rigid V‐shaped structure. DNDTBI exhibited higher electron‐donating ability than singly sulfur‐inserted PBI derivatives owing to the antibonding interaction between the two neighboring sulfur atoms.